URGENSI KONSELING LINTAS AGAMA DAN BUDAYA SEBAGAI UPAYA PREVENTIF PRILAKU RASISME PADA REMAJA - Putri Hanah Anggara; Ilmiyati Refi Fadlia (Jurnal Tawadhu, 2023)
This study aims to look at the urgency of cross-religious and cultural counseling as an effort to prevent racist behavior in adolescents. The research method used is literature study by clarifying and analyzing discussions related to cross-religious and cultural counseling as an effort to prevent racism in adolescents. The results of the study show that cross-religious and cultural counseling can be carried out in various ways such as instilling concepts of understanding tolerance and mutual respect among people, then for youth to participate in educational webinars that contain multi-age values ??as a foundation for preventing racist behavior.